2014
DOI: 10.1007/s00125-014-3413-7
|View full text |Cite|
|
Sign up to set email alerts
|

Pancreatic T cell protein–tyrosine phosphatase deficiency affects beta cell function in mice

Abstract: Aims/hypothesis T cell protein tyrosine phosphatase (TCPTP, encoded by PTPN2) regulates cytokine-induced pancreatic beta cell apoptosis and may contribute to the pathogenesis of type 1 diabetes. However, the role of TCPTP in pancreatic endocrine function and insulin secretion remains largely unknown. Methods To investigate the endocrine role of pancreatic TCPTP we generated mice with pancreas Ptpn2/TCPTP deletion (panc-TCPTP KO). Results When fed regular chow, panc-TCPTP KO and control mice exhibited compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…In STAT3 signaling, phosphosites in the mitogen-activated protein kinase 3 (Mapk3) and mitogen-activated protein kinase 1 (Mapk1) at Y205 and Y185 were upregulated, whereas dual specificity mitogen-activated protein kinase 2 (Map2k2) at S293 and proto-oncogene tyrosine-protein kinase (Src) were detected with significant downregulated phosphosites on proteins at 15 min of GSIS. Activated STAT3 phosphorylation and signaling enhanced GSIS in PBCs (37). The Rho family of small GTPase-mediated mTOR signaling is well known to be activated by glucose (38), and in the acute phase response signaling implicated in type 2 diabetes and the dysfunction of FIG.…”
Section: Gene Ontology Analysis Of Post-translationally Modified Protmentioning
confidence: 98%
“…In STAT3 signaling, phosphosites in the mitogen-activated protein kinase 3 (Mapk3) and mitogen-activated protein kinase 1 (Mapk1) at Y205 and Y185 were upregulated, whereas dual specificity mitogen-activated protein kinase 2 (Map2k2) at S293 and proto-oncogene tyrosine-protein kinase (Src) were detected with significant downregulated phosphosites on proteins at 15 min of GSIS. Activated STAT3 phosphorylation and signaling enhanced GSIS in PBCs (37). The Rho family of small GTPase-mediated mTOR signaling is well known to be activated by glucose (38), and in the acute phase response signaling implicated in type 2 diabetes and the dysfunction of FIG.…”
Section: Gene Ontology Analysis Of Post-translationally Modified Protmentioning
confidence: 98%
“…Recently, the role of PTPN2 in pancreatic endocrine function and insulin secretion was explored. In a study by Xi et al the deficiency in PTPN2 expression by knockout affected beta cell function in mice (Xi et al, 2015 ). The reduced insulin secretion wass associated with a decreased insulin content and glucose sensing, which showed that STAT3 could be a relevant target for the PTPN2 phosphatase regulation in the pancreas (Xi et al, 2015 ).…”
Section: Genetic Variations Of Ptpn2 and mentioning
confidence: 99%
“…In a study by Xi et al the deficiency in PTPN2 expression by knockout affected beta cell function in mice (Xi et al, 2015 ). The reduced insulin secretion wass associated with a decreased insulin content and glucose sensing, which showed that STAT3 could be a relevant target for the PTPN2 phosphatase regulation in the pancreas (Xi et al, 2015 ). PTPN2 regulates insulin signaling by inactivating its receptor through de-phosphorylation of the insulin receptor β-chain in conjunction with the PTP1B phosphatase.…”
Section: Genetic Variations Of Ptpn2 and mentioning
confidence: 99%
“…All these findings show that decreased PTPN2 expression sensitizes beta-cells to apoptosis induced by danger signals, and SNPs within PTPN2 that evoke decreased expression or function may increase the risk of T1DM (8). In addition to apoptosis, insulin secretion is also potentially affected by PTPN2; a previous study found that PTPN2 knockout in mice affected beta-cell function and led to decreased insulin secretion (79).…”
Section: Ptpn2mentioning
confidence: 89%